STRATEGI PELIBATAN MASYARAKAT DALAM PENGAWASAN PEMILU DI INDONESIA - Joni Zulhendra , (Normative Jurnal Ilmiah Hukum, 2019)
Community involvement in election monitoring is a necessity as well as an obligation. Participatory supervision by the community is one of the important pillars in carrying out the controlling function of elections. One way that is considered efficient and effective is through a public approach by utilizing application-based information technology and social media. The sophistication of today's technology cannot be denied, especially since its development is very fast. There are several models of election monitoring strategies in involving the community, Mapping and strengthening participants, Determining appropriate information content, Effective delivery of information, Panwaslu as a facilitator.